Sealant behavior of gasketed segmental tunnel lining – Conceptual model. Issue 4 (August 2016) - Shalabi, Faisal I.; Cording, Edward J.; Paul, Stanley L.
Abstract: Gasket sealant behavior along joints of concrete tunnel lining depends on gasket‐gasket and gasket‐groove contact loads, bonding between gasket and groove, and gasket lateral extrusion. As the gaskets are made of polymers, gasket contact loads are expected to drop with time due to relaxation. Reduction in the contact load with time is expected to affect the gasket sealant capacity. Gasket‐gasket contact loads depend on many factors such as: stiffness of the gasket material, gasket shape and volume, groove size and configuration, gasket base configuration, and the amount of gasket compression. In this work, the mechanical and sealant behavior of gaskets in grooves were investigated. Two types of gaskets were considered: open base gasket for low design water pressure (less than 600 kPa), and closed base gasket for high water pressure (up to 4###, 000 kPa). The work focused on gasket‐in‐groove load deformation behavior and gasket sealant potential including the effect of gasket contact loads, relaxation, extrusion, and the change in joint gap during water pressurization. The effect of gasket base conditions (fingers base vs. closed base) on the gasket sealant behavior was also considered in this work. A conceptual model was developed that explains the leakage of the gasket as water pressure is applied.